A review on the industrial wastewater with the efficient treatment techniques - Kumar, Anil; Thakur, Avinash; Panesar, Parmjit Singh (Chemical papers, 2023)
Nowadays, a debate related to water pollution is going on due to its growing noticeable effects on the ecosystem. The treatment of industrial wastewater has become a great environmental concern because of the speedy progress of economy and industries. Water pollution due to the presence of heavy metals (Zn, Cu, Pb, Ni, Cd, Hg, etc.) has a significant public health hazard and also exhibits various types of toxicological appearances. Several remediation technologies have been adapted/investigated revitalizing polluted wastewater without impeding the environment. The suitability and applicability of various separation techniques (such as chemical precipitation, adsorption, electrochemical treatment, and liquid membrane) were discussed in this study. The focus of this literature is mainly to elucidate about the treatment performance of various separation technologies and their toxic impacts on the environment and human health. Hence, this review article has abridged and elucidated the most topical literature studies and suggestions about the heavy metal ions from the aqueous toxins and their treatment techniques. Conclusively, a promising technique called emulsion liquid membrane (ELM) along with its recent advances has been proposed as an efficient treatment technique for wastewater remediation.